1999
DOI: 10.1021/ja9914240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Aqueous Decomposition of Trichloroethylene Oxide

Abstract: The aqueous decomposition of trichloroethylene (TCE) oxide is shown to involve both pH-independent and hydronium ion-dependent regions. C−C bond scission is a major reaction at all pH values. Disappearance of TCE oxide is the rate-determining step for the formation of CO under the conditions studied. The product distribution of CO and three carboxylic acids (HCO2H, Cl2CHCO2H, and glyoxylic acid) did not change considerably over the pH range of −1.5−14, in general, even though the hydrolysis mechanism changes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(101 citation statements)
references
References 45 publications
8
92
1
Order By: Relevance
“…In addition, vinyl compounds with good leaving groups can form epoxides that rearrange, e.g. to ␣-halocarbonyls (18,19).…”
Section: Oxidationsmentioning
confidence: 99%
“…In addition, vinyl compounds with good leaving groups can form epoxides that rearrange, e.g. to ␣-halocarbonyls (18,19).…”
Section: Oxidationsmentioning
confidence: 99%
“…The oxidation product of pyridine is inactive, but the final product of hexane oxidation, 2,5-hexanedione, can cross-link proteins. To complicate matters, it is also not unusual for multiple products with varying metabolic activity to be formed from P450 reactions on a single substrate as with trichloroethylene [36,37] (Fig. 5C).…”
Section: Catalysis By P450smentioning
confidence: 99%
“…B, during metabolism of other chemicals, P450s may inactivate a toxicant, such as observed with pyridine (solvent) (heteroatom oxygenation), or activate a chemical to a toxic metabolite, as observed with hexane (solvent) (hydroxylation and further oxidation of the alcohols to ketones). C, in some cases, P450s may produce a mixture of deactivated and toxic products, as is the case with trichloroethylene (solvent, common contaminant in waste dumpsites) (epoxidation followed by rearrangement to a more reactive product [36], and olefin oxidation accompanied by a 1,2 migration of chloride ion to the deactivated product chloral, which is actually a sedative [37]). Despite the differences in reaction types, all reaction mechanisms proceed via the generalized P450 catalytic cycle shown in Fig.…”
Section: Catalysis By P450smentioning
confidence: 99%
“…Humans are efficient at glucuronidating TCOH relative to rodents, although impaired ability for glucuronidation reactions is relatively frequent in the human population (Templin et al, 1993;Green et al, 1997). Recent studies indicated that dichloroacetyl chloride is generated from TCE oxide and can be trapped with lysine to form N ⑀ -dichloroacetyllysine (Cai and Guengerich, 1999). The acyl chloride subsequently decomposes to form dichloroacetic acid (DCA).…”
mentioning
confidence: 99%